2017
DOI: 10.1111/vco.12293
|View full text |Cite
|
Sign up to set email alerts
|

Somatic SNPs of the BRCA2 gene at the fragments encoding RAD51 binding sites of canine mammary tumors

Abstract: Mammary tumors are the most common tumor type both in women and in female dogs. In women, heritable breast cancers have been linked mutations in the breast cancer susceptibility gene BRCA2 and it contains eight BRC repeats in exon 11 that bind to RAD51. In this study, we investigated the sequence variations of BRC1-BRC8 and C-terminus of canine BRCA2 gene. From a total of 64 canine patients with mammary tumors, 31 mammary tumors with benign and malign carcinomas and the 3 normal mammary glands were used for th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
31
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(34 citation statements)
references
References 27 publications
2
31
0
Order By: Relevance
“…Studies of in vitro and in vivo assays demonstrated that canine BRCA2 mutations located in BRC3 do affect interactions with RAD51. Similarly as their corresponding human BRCA2 variants (p.T1430P and p.K1440R), the SNPs in BRC3 domain of canine BRCA2 (p.T1425P and p.K1435R) also showed to affect the interaction with the RAD51 protein . The canine BRCA2 polymorphism that result in amino acid change p.T1425P showed evidences of reducing the binding strength with RAD51 and probably affect the full‐length of BRC functions.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…Studies of in vitro and in vivo assays demonstrated that canine BRCA2 mutations located in BRC3 do affect interactions with RAD51. Similarly as their corresponding human BRCA2 variants (p.T1430P and p.K1440R), the SNPs in BRC3 domain of canine BRCA2 (p.T1425P and p.K1435R) also showed to affect the interaction with the RAD51 protein . The canine BRCA2 polymorphism that result in amino acid change p.T1425P showed evidences of reducing the binding strength with RAD51 and probably affect the full‐length of BRC functions.…”
Section: Discussionmentioning
confidence: 96%
“…Differently, the canine BRCA2 polymorphism that result in amino acid change p.K1435R, as well as its analogous human variant p.K1440R, revealed stronger interactions with canine RAD51 and human RAD51, inhibiting RAD51 self association to a greater extent than the wild‐type BRC3. Therefore, it is suggested that these mutations in dogs and humans might be associated to mammary tumors as a result of their effect on the regulation of RAD51 recruitment …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, they later analyzed polymorphisms in canine BRC3 and in dogs of multiple breeds: they showed significant reduction of binding strength of BRC3-4 containing the a specific allele version (1425P) with RAD51 (all following polymorphisms summarized in Table 2) [53]. More recently, Ozmen et al investigated the sequence variations of BRC1-BRC8 and Cterminus of canine BRCA2 [54] and found multiple SNPs in exon 11 and one insertion/deletion polymorphism in exon 27. Further in silico investigations added to speculation that a specific variation in BRC3 is the most likely to affect the RAD51 binding strength.…”
Section: Polymorphisms Found In the Canine Brca2 Genementioning
confidence: 99%
“…In canine studies, although several mutations have been detected in BRCA2, canine RAD51 (cRAD51) mutations have not been reported. However, a recent report identified the presence of multiple cRAD51 mutations in canine mammary tumours, and predicted that A209S and T225S mutations in cRAD51 might influence its interactions with the “partner and localizer of BRCA2” (PALB2).…”
Section: Introductionmentioning
confidence: 99%